1973
DOI: 10.1111/j.1399-0039.1973.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Standardization of the Conditions for Micro‐Lymphocyte Cultures

Abstract: Experiments were performed to establish optimal conditions for specific and non‐specific lymphocyte transformation in vitro, in cultures containing 1–3 × 105 human lymphocytes. The stimulation as measured by 14C‐thymidine incorporation was evaluated when using various methods of lymphocyte purification and different numbers of contaminating erythrocytes, different kinds of tubes, serum from different sources, and varying PHA concentrations. Furthermore, the dependence of the 14C‐thymidine incorporation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Mononuclear cells isolated from peripheral blood, spleen or lymph nodes from patients with NHL, CLL or ALL were used for this study*. Cells were isolated by Ficoll-Isopaque centrifugation of defibrinated blood (Du Bois et al 1973). Cells were freed from tissue fragments by teasing and mincing through tantalum gauze.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mononuclear cells isolated from peripheral blood, spleen or lymph nodes from patients with NHL, CLL or ALL were used for this study*. Cells were isolated by Ficoll-Isopaque centrifugation of defibrinated blood (Du Bois et al 1973). Cells were freed from tissue fragments by teasing and mincing through tantalum gauze.…”
Section: Cellsmentioning
confidence: 99%
“…The capacity to stimulate allogenic cells in one-way mixed lymphocytic culture was determined as described previously (Du Bois et al, 1973). Tests were performed in microtest culture plates (round bottom), each well containing 4 x lo4 lymphocytes of both responding and stimulating cells in RPMI-I 640 medium (Flow Laboratories, Irvine, Ayrshire, Scotland), buffered with bicarbonate and supplemented with 20% heat-inactivated pooled human serum.…”
Section: Mixed Lymphocyte Culturementioning
confidence: 99%
“…Some of the currently available systems (Sengar & Terasaki 1971, Hartzmann et al 1971, Du Bois et al 1973) already represent a considerable development in this direction. In this context, we have made some efforts towards further reduction o,f cell numbers, media volumes and harvest-ing times.…”
mentioning
confidence: 99%
“…We have recently described our investigations on the optimalization of lymphocyte cultures; thus, a standardized technique was developed yielding optimal results with limited numbers of lymphocytes (1-3X 105) (Du Bois et al 1973).…”
mentioning
confidence: 99%
“…I t was found that a maximal response in the presence of soluble antigen or allogeneic cells is critically dependent upon the number of lymphocytes sedimented per unit surface area, both greater and smaller cell numbers giving lower responses (Du Bois et al 1973, Schellekens & Eijsvoogel 1971) .This may be caused by two counteracting phenomena. Firstly, close membrane contact of the lymphocyte may be a prerequisite for optimal reactivity (Moorhead et al 1967, Leventhal & Oppenheim 1969.…”
mentioning
confidence: 99%